Synthesis and Biological Activity of Novel 1-(Substituted Phenoxyacetoxy) Alkyl Phosphonates and Phosphinates - Meng, Liping; Joshi, Rajendra; Li, Meiqiang; He, Hongwu (Journal of Nepal Chemical Society, 2009)
To investigate the influence of nitro group on the biological activity of phenoxyacetoxy phosphonates and phosphinates, a series of novel 1-(substituted phenoxyacetoxy) alkyl phosphonates and phosphinates were synthesized and screened for herbicidal activity and plant growth regulatory activity. Compounds 5a, 5b and 5j exhibited notable bioactivity. Results indicated that nitro groups had a great influence on the biological activity, and the improvement of biological activity required a reasonable combination of a nitro group and other substituents. DOI: 10.3126/jncs.v23i0.2092 J. Nepal Chem. Soc., Vol. 23, 2008/2009 Page: 11-20